Scanning electron microscope analysis of internal adaptation of materials used for pulp protection under composite resin restorations - Peliz, Maria Inez Lemos; Duarte Jr., Sillas [UNESP]; Dinelli, Wellington (Wiley, 2005)
Purpose: The aim of this study was to evaluate the interfacial microgap with different materials used for pulp protection. The null hypothesis tested was that the combination of calcium hydroxide, resin-modified glass ionomer, and dentin adhesive used as pulp protection in composite restorations would not result in a greater axial gap than that obtained with hybridization only. Materials and Methods: Standardized Class V preparations were performed in buccal and lingual surfaces of 60 caries-free, extracted human third molars. The prepared teeth were randomly assessed in six groups: (1) Single Bond (SB) (3M ESPE, St. Paul, MN, USA); (2) Life (LF) (Kerr Co., Romulus, MI, USA) + SB; (3) LF + Vitrebond (VT) (3M ESPE) + SB; (4) VT + SB; (5) SB + VT; (6) SB + VT + SB. They were restored with microhybrid composite resin Filtek Z250 (3M ESPE), according to the manufacturer's instructions. However, to groups 5 and 6, the dentin bonding adhesive was applied prior to the resin-modified glass ionomer. The specimens were then thermocycled, cross-sectioned through the center of the restoration, fixed, and processed for scanning electron microscopy. The specimens were mounted on stubs and sputter coated. The internal adaptation of the materials to the axial wall was analyzed under SEM with × 1,000 magnification. Results: The data obtained were analyzed with nonparametric tests (Kruskal-Wallis, p ≤ .05). The null hypothesis was rejected. Calcium hydroxide and resin-modified glass ionomer applied alone or in conjunction with each other (p < .001) resulted in statistically wider microgaps than occurred when the dentin was only hybridized prior to the restoration. ©2005 BC Decker Inc.
Keywords: biomedical and dental materials; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; calcium hydroxide; dentin bonding agent; Filtek Z250; glass ionomer; Life (dental material); resin; resin cement; single bond; Vitrabond; chemistry; classification; clinical trial; controlled clinical trial; controlled study; dental surgery; dentin; enamel; endodontics; human; randomized controlled trial; scanning electron microscopy; surface property; ultrastructure; Bisphenol A-Glycidyl Methacrylate; Calcium Hydroxide; Composite Resins; Dental Cavity Lining; Dental Cavity Preparation; Dental Enamel; Dental Materials; Dental Restoration, Permanent; Dentin; Dentin-Bonding Agents; Glass Ionomer Cements; Humans; Marginal Adaptation (Dentistry); Microscopy, Electron, Scanning; Resin Cements; Surface Properties